A study conducted in a tertiary care hospital to assess the cardiac function in paediatric beta thalassemia major patients and correlation with serum ferritin levels which are indicative of chelation status of the patients - Rao, Jayashree Satish; K, Nagendra (Indian Journal of Child Health, 2023)
Background: Thalassemia is one of the common inherited blood disorders and Beta Thalassemia Major is a homozygous form of deficiency of beta globin chain synthesis causing severe transfusion-dependent anemia, manifesting between 6 and 24 months of life. Objectives: The objective of the study is to study the pattern of cardiac function in children and adolescents with beta-thalassemia major by 2D Echocardiography and its correlation with serum ferritin levels. Methods: Fifty subjects diagnosed with Beta Thalassemia Major, after applying the inclusion and exclusion criteria were included in Group 1, and 50 age and gender-matched subjects without Beta Thalassemia Major were included in Group 2. Serum ferritin level was measured using Cobas 6000 analyzer. Echocardiography was done with the following parameters: Posterior wall thickness-diastolic (PWT-D), posterior wall thickness- systolic (PWT-S), left ventricular internal diameter-diastole (LVID-D), left ventricular internal diameter-systole (LVID-S), septal thickness and tricuspid regurgitation (TR) velocity. Results: Among the 50 study population, 28 children belonged to the age group 5–10 years (56%) and 22 children belonged to the age group 10–15 years (44%). Among the cardiac parameters, The PWT-D, PWT-S, LVID-D, LVID-S, TR velocity, and septal thickness values were higher in the cases group compared to the control group with p values suggesting strong significance. The ejection fraction in the cases was lower than the control group with a strongly significant p-value. Conclusion: Children with thalassemia have impaired cardiac function and the degree of dysfunction is correlated to the serum ferritin levels. Regular transfusion and adequate chelation are essential to decrease morbidity and mortality.